Cyberculture and the subaltern : weavings of the virtual and real - Gajjala, Radhika, 1960- (Lanham, Md. : Lexington Books, 2013)
'Through inter-disciplinary lenses enabled by cultural studies and feminist methodologies, Cyberculture and the Subaltern: Weavings of the Virtual and Real, edited by Radhika Gajjala, looks at online microfinance, new technologies, virtual world marketing, and handloom contexts from India and Africa in relation to development discourse that posits a binary between'tradition' and modernity. Through actual (auto)ethnographic engagement in these contexts, the contributors to this volume reveal the interdependence of the economic, political, cultural, and social in the production of the subaltern online'--
'Cyberculture and the Subaltern: Weavings of the Virtual and Real, edited by Radhika Gajjala, maps how voice and silence shape online space in relation to offline actualities. Thus, it weaves the virtual and real in relation to so-called old and new technologies using globalization and technology as the frame for examination. Implicit in this investigation is the question of how offline actualities and online cultures are in turn shaped by online hierarchies, as well as different kinds of local access to global contexts. This book reveals the logic of particular global-local directions that emerge within digital, transnational capital and labor flows. To this end, the contributors to this volume examine various sites and intersections through critical lenses enabled by conversations and writings in subaltern studies, affect theory, postcolonial feminist theory, critical cultural studies, communication studies, critical development studies, and science and technology studies. Contexts explored in this collection include microfinance online, handloom contexts from India and Africa in relation to development discourse, new technologies, and virtual world marketing. Through actual auto-ethnographic engagement, Cyberculture and the Subaltern reveals the interdependence of the economic, political, cultural, and social in the production of the subaltern online'--
Empowerment, Socioeconomic Globalization, and Digital Divides -- by Radhika Gajjala -- Chapter 1. Producing the Global: Microfinance Online -- by Radhika Gajjala, Franklin Nii Yartey, and Anca Birzescu -- Chapter 2. Philanthropist or Investor? Microlending to the Other -- by Radhika Gajjala, Anca Birzescu, and Franklin Nii Yartey -- Chapter 3. Snapshots from Sari Trails: Cyborgs Old and New -- by Radhika Gajjala, with Rad Zabibha -- Chapter 4. Framing the Loom -- by Radhika Gajjala, Seemanthini Niranjana, and B. Syamasundari -- Chapter 5. Kente Cloth and Adinkra in the Global Market -- by Precious Yamaguchi and Franklin Nii Yartey -- Conclusion -- by Radhika Gajjala.
Includes index and bibliography : p.163-178.
Keywords: Microfinance -- India; Microfinance -- Africa; Internet marketing -- India; Internet marketing -- Africa